Comparison of Outcome of three Different Approaches for Supracondylar Humerus Fractures in Children - Muhammad Zeb Khan, Muhammad Ikram, Raja Adnan Ashraf, Saqib Jan Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction Supracondylar humerus is one of the most common elbow fractures in children. It accounts for about 60% of all the elbow fracture. It is a challenging orthopedic presentation. It is more common in the children younger than 15. The bending structure and weak metamorphic sclerotin of distal humerus are the underlying cause behind these fractures. Fractures are classified according to the Gartland’s criteria. Study design: It is a retrospective study conducted at Sahara Medical College, Narowal and Pakistan Railway General Hospital, Rawalpindi for duration of six months from August 2022 to January 2023. Material and Methods: The patients were aware of the study objective. The demographic features of each selected patient were recorded. There were total 150 patients included in this study. Patients were divided into three groups on the basis of type of approach used for the treatment of supracondylar humerus fracture; lateral approach, medial approach and posterior approach as group A, B and C respectively. Results: The average age of patients was 7.61±4.5, 7.2±3.6 and 6.5±4.5 years for group A, B and C respectively. The reason of fracture was determined and the data revealed that most of the injuries were related to sports. P value was calculated and the data was statistically significant. Conclusion: Our results suggest that as compared to posterior and medial, lateral approach is better as it showed significant radiological and functional outcomes. It can be used by surgeons as it takes less time and the complications rate is lower. Keywords: lateral approach, supracondylar humerus and posterior approach.